Endoscopy, histology and electron microscopy analysis of foetal membranes in pregnant South American plains vizcacha reveal unusual excrescences on the yolk sac - Giacchino, Mariela (2018)
The South American hystricognathe Lagostomus maximus is a fossorial rodent whose females show unique reproductive characteristics. They have a 155-day long gestation, show massive polyovulation and a selective process of embryonic resorption in the first half of gestation. In order to explore and perform an in-situ characterization of the reproductive tract, we visualized internal structures through ultrasonography and video-endoscopy in pregnant and non-pregnant females. We describe the finding of protruding structures that lie on the yolk sac and their histological and ultrastructural characterization. The placenta was covered with whitish, small pearl-shaped structures. These structures were also seen on the extra-embryonic space, being the amnion and the umbilical cord free of them. Pearl-shaped structures were composed with loose connective tissue, lacked blood vessels, and showed collagen fibers organized in a spiral form. They were anchored by pedicles to the villous surface of the extraembryonic membrane. We discuss the biological and evolutionary meaning of the pearl-shaped structures that relate L. maximus to the African origin of the South American hystricognathe fauna.